Formação docente sobre educação das relações étnico-raciais: retalhos do processo de implementação da Lei 10.639/2003 No município de São Gabriel da Palha/ES - Pacheco, Lizie (2021)
The present study aimed to investigate the continuing education on Education of Ethnic-Racial Relations of teachers of the Municipal Education Network of São Gabriel da Palha/ES, and its implications on teaching practice. Such intention originated from the following research problem: how has the teaching of African and Afro-Brazilian history and culture been guaranteed in the schools of the São Gabriel da Palha/ES Municipal Education Network? And to what extent this theme is addressed in the continuing education of their teachers? Therefore, the study is based on the Freirian concept of education, as well as the studies of Stuart Hall, Bell Hooks, Kabengele Munanga, Luiz Fernandes de Oliveira and Nilma Lino Gomes to discuss the continuing education of teachers from the perspective of ethnic-racial relations. The qualitative research and the collaborative-critical action research are used as methodology, having as participants/collaborators three teachers of the Municipal Education Network of São Gabriel da Palha/ES. From the data produced with the documentary analysis of legal provisions relating to the Education of Ethnic-Racial Relations, with the application of questionnaires and interviews and with the realization of a formative moment, it was prepared the Plan for Continuing Education of Teachers on Education of Ethnic-Racial Relations, which is configured as the educational product of this study. The results obtained indicate that Law 10.639/2003 has already been implemented in the municipality in question, but it needs to advance towards implementation. Teachers are aware of the existence of the law, but need to know its guidelines and re-signify their teaching practices. The continuing education on REER shows itself as a viable and necessary alternative for the implementation of Law 10.639/2003 in the municipality of São Gabriel da Palha/ES, since until then the teaching of African and Afro-Brazilian history and culture has been addressed only sporadically through projects and isolated and discontinuous actions. Thus, it is expected that the educational product of this research will contribute to reverse this situation.